2015
DOI: 10.1186/s12906-015-0807-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and hypolipidemic activities of aqueous extract of flowers from Nycantus arbor-tristis L. in male mice

Abstract: BackgroundBoiled aqueous extract of flowers (AEF) from Nyctanthes arbor-tristis L. are used in Sri Lankan traditional Ayruvedic Medicine to manage diabetes mellitus. AEF has widely been used as a folk medicine for the treatment of various ailments due to its therapeutic activity. However, little is known concerning therapeutic activity of the extract as well as its underline mechanisms and safety. Diabetes is known to increase low-density cholesterol and decrease high-density cholesterol thus triggering corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…A higher hypoglycemic effect at doses >100 mg/kg was expected, but when a dose of 200 mg/kg was administrated a lower reduction in blood glucose levels was observed. This dose-independent effect could be linked to the presence of some other constituents in the aqueous extract which at high concentration could be acting as antagonist agents of the hypoglycemic effect as described in other aqueous plants extracts (Rangika et al, 2015). In phytochemical screening of aqueous extract, we observed the moderate presence of saponins and alkaloid.…”
Section: Discussionsupporting
confidence: 55%
“…A higher hypoglycemic effect at doses >100 mg/kg was expected, but when a dose of 200 mg/kg was administrated a lower reduction in blood glucose levels was observed. This dose-independent effect could be linked to the presence of some other constituents in the aqueous extract which at high concentration could be acting as antagonist agents of the hypoglycemic effect as described in other aqueous plants extracts (Rangika et al, 2015). In phytochemical screening of aqueous extract, we observed the moderate presence of saponins and alkaloid.…”
Section: Discussionsupporting
confidence: 55%
“…Dietary antioxidants offer protection against ROS-/RNS-induced stress and damage through their direct actions based on mechanisms complementary to the functions of enzymatic antioxidants in the human body as well as their close association and support to primary and secondary enzymes (Durackova, 2010). Among these antioxidant species, antioxidative polysaccharides extracted from various raw materials in nature and their derived products have attracted increasing attention (Li et al, 2014;Jiang et al, 2015;Rangika et al, 2015). Among these antioxidant species, antioxidative polysaccharides extracted from various raw materials in nature and their derived products have attracted increasing attention (Li et al, 2014;Jiang et al, 2015;Rangika et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There are many dietary antioxidants that can be sourced from nature including protein-, polysaccharide-or lipid-based substances and small molecule phytochemicals such as vitamins and polyphenols (Lobo et al, 2010;Nimse & Pal, 2015). Among these antioxidant species, antioxidative polysaccharides extracted from various raw materials in nature and their derived products have attracted increasing attention (Li et al, 2014;Jiang et al, 2015;Rangika et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Results the present study indicated that AEF possess hypoglycemic and hypolipdemic properties. Therefore, AEF could be used as an alternative medicine in management of diabetes mellitus (Rangika et al, 2015).…”
Section: Boiled Aqueous Extract Of Flowers (Aef) Frommentioning
confidence: 99%